LysoPE mediated by respiratory microorganism Aeromicrobium camelliae alleviates H9N2 challenge in mice - Qingsong Yan; Junhong Xing; Ruonan Zou; Mingjie Sun; Boshi Zou; Yingjie Wang; Tianming Niu; Tong Yu; Haibin Huang; Wentao Yang; Chunwei Shi; Guilian Yang; et al. (Veterinary Research, 2024)
Abstract Influenza remains a severe respiratory illness that poses significant global health threats. Recent studies have identified distinct microbial communities within the respiratory tract, from nostrils to alveoli. This research explores specific anti-influenza respiratory microbes using a mouse model supported by 16S rDNA sequencing and untargeted metabolomics. The study found that transferring respiratory microbes from mice that survived H9N2 influenza to antibiotic-treated mice enhanced infection resistance. Notably, the levels of Aeromicrobium were significantly higher in the surviving mice. Mice pre-treated with antibiotics and then inoculated with Aeromicrobium camelliae showed reduced infection severity, as evidenced by decreased weight loss, higher survival rates, and lower lung viral titres. Metabolomic analysis revealed elevated LysoPE (16:0) levels in mildly infected mice. In vivo and in vitro experiments indicated that LysoPE (16:0) suppresses inducible nitric oxide synthase (INOS) and cyclooxygenase-2 (COX2) expression, enhancing anti-influenza defences. Our findings suggest that Aeromicrobium camelliae could serve as a potential agent for influenza prevention and a prognostic marker for influenza outcomes.